Alcohol Consumption in Elderly People across European Countries: results from the Food in Later Life Project - Almeida, Maria Daniel Vaz de (2005)
The aim of this paper is to identify social and cultural aspects of alcohol consumptionin a sample of older people living in their own homes, in eight different Europeancountries. We explore several aspects of alcohol consumption, establishingcomparisons between genders, age groups and living circumstances. The phenomenonof alcohol consumption within these countries and cultures is compared inorder to gain a better understanding of similarities and differences.